Powieść uniwersytecka Alicji Iwańskiej - Wal, Anna (Postscriptum Polonistyczne, 2020)
The paper discusses the novel Baśń amerykańska [An American Fairy Tale] by Alicja Iwańska, a Polish writer and sociologist who worked at American universities for many years. The paper discusses the picture of the academic community at a state university in the USA in the 1960s and the way in which it is presented, which makes it possible to classify the text as a campus novel, which is an extremely popular genre in English-language literature. The paper also points to the author’s demythologising view of the USA, challenging the American myth characteristic of the Polish awareness.